epic3: National Evidence-Based Guidelines for Preventing Healthcare-Associated Infections in NHS Hospitals in England - Loveday, H.P.; Wilson, J.A.; Pratt, R.J.; Golsorkhi, M.; Tingle, A.; Bak, A.; Browne, J.; Prieto, J.; Wilcox, M. (The Journal of hospital infection, 2014)
National evidence-based guidelines for preventing healthcare-associated infections (HCAI) in National Health Service (NHS) hospitals in England were originally commissioned by the Department of Health and developed during 1998–2000 by a nurse-led multi-professional team of researchers and specialist clinicians. Following extensive consultation, they were first published in January 20011 and updated in 2007.2 A cardinal feature of evidence-based guidelines is that they are subject to timely review in order that new research evidence and technological advances can be identified, appraised and, if shown to be effective for the prevention of HCAI, incorporated into amended guidelines. Periodically updating the evidence base and guideline recommendations is essential in order to maintain their validity and authority. The Department of Health commissioned a review of new evidence and we have updated the evidence base for making infection prevention and control recommendations. A critical assessment of the updated evidence indicated that the epic2 guidelines published in 2007 remain robust, relevant and appropriate, but some guideline recommendations required adjustments to enhance clarity and a number of new recommendations were required. These have been clearly identified in the text. In addition, the synopses of evidence underpinning the guideline recommendations have been updated. These guidelines (epic3) provide comprehensive recommendations for preventing HCAI in hospital and other acute care settings based on the best currently available evidence. National evidence-based guidelines are broad principles of best practice that need to be integrated into local practice guidelines and audited to reduce variation in practice and maintain patient safety. Clinically effective infection prevention and control practice is an essential feature of patient protection. By incorporating these guidelines into routine daily clinical practice, patient safety can be enhanced and the risk of patients acquiring an infection during episodes of health care in NHS hospitals in England can be minimised.